Global energy circulation, Turkey's geographical location and petropolitics - Akdemir, Ilhan Oguz (Elsevier Science Bv, 2011)
The world map is being designed. The reason behind this turns around the new movement that is centred on the Caspian Sea and Middle East. We can might different subjective analysis about these three broad categories. It is a common assumption that the energy transfer will change the national borders in the Middle East and influence Turkey. The main variable that will influence the future of Turkey is about the decision on the energy transfer pipelines that will transfer the energy between the Asian and the European countries. The direction of the pipelines from the Middle Asia will be the key for the geopolitical importance of Turkey. Besides, the road that the African gas will follow is closely related with Turkey. Turkey posses one of the strategic areas of the world in terms of its geographical location. However, geopolitics location and geographic location are different from each other that are generally confused. It is important to work for country's relative location's being strong as a country. In fact while assessing Turkey's diplomatic and geopolitical interests, one should consider the importance of the Afro-Eurasia centered energy transfer and the fact that the results cannot be taken only through diplomatic means. It is important to read the map through considering culture and politics rather than sole diplomatic lenses. Besides, while defining the energy politics of the country, it is important to consider the fact that petroleum and gas can be consumed in the long run. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of The 2nd International Geography Symposium-Mediterranean Environment
2nd International Geography Symposium-Mediterranean Environment -- JUN 02-05, 2010 -- Antalya, TURKEY
Keywords: Turkey; Energy; Geography; Geopolitic; Petropolitic; Geographical Location